Relationship maintenance strategies in the coach-athlete relationship: the development of the COMPASS Model - Rhind, D. J.; Jowett, S. (Journal of Applied Sport Psychology, 2010)
The investigation of relationship maintenance strategies has received considerable attention in various types of dyads including romantic, marital, and familial relationships. No research, however, has yet investigated the use of maintenance strategies in the coach-athlete partnership. Thus, this study aimed to investigate coaches` and athletes` perceptions of the strategies they use to maintain relationship quality. Twelve one-to-one interviews with coaches (4 males and 2 females) and athletes (2 males and 4 females) were conducted. The interviews were structured based on the factors within Jowett's (2007) 3+1C conceptualization of the coach-athlete relationship (i.e., closeness, commitment, complementarity, and co-orientation). Deductive and inductive content analysis revealed seven main categories: conflict management, openness, motivation, positivity, advice, support, and social networks. The COMPASS model was developed based on this analysis and was offered as a theoretical framework for understanding how coaches and athletes might maintain the quality of their relationships.